Regulatory Roles of Phospholipase A2 Enzymes and Bioactive Lipids in Mast Cell Biology - Taketomi, Yoshitaka; Murakami, Makoto (Frontiers in Immunology, 2022)
Lipids play fundamental roles in life as an essential component of cell membranes, as a major source of energy, as a body surface barrier, and as signaling molecules that transmit intracellular and intercellular signals. Lipid mediators, a group of bioactive lipids that mediates intercellular signals, are produced via specific biosynthetic enzymes and transmit signals via specific receptors. Mast cells, a tissue-resident immune cell population, produce several lipid mediators that contribute to exacerbation or amelioration of allergic responses and also non-allergic inflammation, host defense, cancer and fibrosis by controlling the functions of microenvironmental cells as well as mast cell themselves in paracrine and autocrine fashions. Additionally, several bioactive lipids produced by stromal cells regulate the differentiation, maturation and activation of neighboring mast cells. Many of the bioactive lipids are stored in membrane phospholipids as precursor forms and released spatiotemporally by phospholipase A2 (PLA2) enzymes. Through a series of studies employing gene targeting and lipidomics, several enzymes belonging to the PLA2 superfamily have been demonstrated to participate in mast cell-related diseases by mobilizing unique bioactive lipids in multiple ways. In this review, we provide an overview of our current understanding of the regulatory roles of several PLA2-driven lipid pathways in mast cell biology.